Land Redistribution in South Africa: Towards Decolonisation or Recolonisation?. (2nd January 2018) - Kepe, Thembela; Hall, Ruth
ABSTRACT: Contrary to populist political discourses, in South Africa the ruling party's approach to land policy is reproducing paternalistic relations that echo apartheid practices and represent the 'colonial present'. This reality stands in stark contrast to the initial aim of land reform, which was conceived as part of a larger project of decolonisation. The latest land redistribution strategy, the Proactive Land Acquisition Strategy, where the state remains the landowner, is no longer consistent with the project of decolonisation. This is because, we argue, land redistribution in South Africa has drifted away from the ideal of social justice; it increasingly displays symptoms of what the 'colonial present' and 'recolonisation'. Party politics, as well as the emergence of a challenge to the ruling party from the left, has prompted a more radical rhetoric, but one that co-exists with deeply conservative practices. This paper argues that the status quo represents a betrayal of the idea of land reform as decolonisation, and that a radical shift in policy and practice is needed in order to align it with a project of decolonisation in South Africa.